Profile of studies of potential drug interactions in Brazilian hospitals: an integrative review of the literature - Adriana Tiemi Yamagata; Roberto Mauro Coelho Barcelos Júnior; Dayani Galato; Micheline Marie Milward De Azevedo Meiners; Emília Vitória Da Silva (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2018)
The risk of drug interaction (DI), especially in the hospital setting, increases along with the number of drugs used by the patient. Studies that evaluate drug interactions based on patient prescriptions are therefore useful to know this risk and guide strategies to improve drug use. The present study is aimed to identify studies that evaluated DI in patients of Brazilian hospitals. As of bibliographic search in several databases, we collected articles describing prescribing evaluations which focused on the analysis and identification of drug interactions in Brazilian hospitals. The search was conducted in 2017 and there was no restriction of publication time. Of a total of 273 articles retrieved, 23 were included for analysis. Most was published after 2010, and the predominant design was cross-sectional studies. The Micromedex® database was the most used to categorize the interactions, and midazolam and fentanyl was the most commonly reported potential DI in the studies. The results may guide futures research which should assess the real harm of IMP in patients and, then, promote the rational use of drugs.